Atividade antifúngica de Stryphnodendron adstringens (Mart.) Coville sobre leveduras de isolados clínicos - Ishida, Kelly (2006)
In natural products, mainly plants, have searched bioactivies compounds which can become an alternative for development of news antifungal agents with fewer side effects, a greater spectrum of action and Low cost. So, the aim of this study was verify the effect of rude extract, fractions, and sub-fractions otained from Stryphnodendron adstringens (Mart.) Coville, known as "barbatimão", on yeasts isolated from vaginal fluid. Of 506 vaginal fluid sampIes, 103 had positive culture on dextrose Sabouraud ágar (20.35%). Ninety and six sampIes were identified as Candida albicans and, six C. non- albicans (1 C. parapsilosis, 1 C. tropicalis and 4 Candida sp). One no concern genus Candida. All yeasts were susceptible to polyenes and, just 7.76% were resistants or dose dependent susceptible. The most of yeast produced acid protease (99%), phospholipase (83%) and hemolysin (91.3%). Adherence on Vero cells was varied, being 67.9% with 50 to 150 yeasts/100 cells, and the most had hydrophilics characteristics. The extracts of S. adstringens showed antifungal activity in concentration above 7.8 µg/mL, however just fungistatic action. The sub-fraction F2.4 inhibited the germinative tube formation in concentrations 15.75 In natural products, mainly plants, have searched bioactivies compounds which can hconic an alternative for development of news antifungal agents with fewer side effects, a ienter spectrum of action and Low cost. So, the aim of this study was verify the effect of rude extract, fractions, and sub-fractions obtained from Stryphnodendron adstringens (Mart.) Coville, known as "barbatirnão", on yeasts isolated from vaginal fluid. Of 506 vaginal fluid umpIes, 103 had positive culture on dextrose Sabouraud ágar (20.35%). Ninety and six anipIes were identified as Candida albicans and, six C. non- albicans (1 C. parapsilosis, 1 C. fropicalis and 4 Candida sp). One no concern genus Candida. All yeasts were susceptible to polycncs and, just 7.76% were resistants or dose dependent susceptible. The most of yeast produced acid protease (99%), phospholipase (83%) and hemoLysin (91.3%). Adherence on Vem edis was varied, being 67.9% with 50 to 150 yeasts/100 cells, and the most had hydrophilics characteristics. The extracts of 8. adstringens showed antifungal activity in onccntration above 7.8 µg/mL, however just fungistatic action. The sub-fraction F2.4 inhibited the germinative tube formation in concentrations 15.75 µg/mL and significative ncrcase of buddings (188.34%) was observed in yeasts treated with 125 µg/mL. Adherence inhibition of yeast on cell and a biotic surface was dependent dose. The sub-fraction F2.4 reduced the cellular surface hydrophobicity. In this study was not possible verify the inhibition of extracellular enzymes activities. Combinations of sub-fraction F2.4 with amphotericin B, nystatin or fluconazole were not synergic. Through optic and scanning cletronic microscopy can be observed the inhibition in pseudohyphal formation and aggiutinant effect of sub-fraction F2.4. Irregularity on cell wall of yeasts treated was observed and transrnission eietronic microscopy showed evidence of the effect of "barbatimão" on yeast wall cdl. Additionally, the macrophage stimulation was verify when the yeasts were tu(ccI previously with 7.8 µg/mL of sub-fraction F2.4 by 2 h, observing increase of 28% iimpared with control group. Cytotoxicity effect ofextracts obtained from "barbatirnão" was hNeaved on Vero and rnacrophages celis with CC50 above 100 µg/mL. On the other hand, for hlood red ccli and Aflemia salina grub the CC50 and DL50 were >1,000 µg/mL, except for subl (ion F2.4, which DL50 was 100 jig/mL. Probably the antifungal activity of sub-fraction 1 /4 is attributed the polyrners proanthocyanidins tri-hydroxylated in ring B and presence of acid Iinked in structure ofpolymer, with median molecular weight of 2,000 15.75 µg/mL and significative ncrcase of buddings (188.34%) was observed in yeasts treated with 125 µg/mL. Adherence inhibition of yeast on cell and a biotic surface was dependent dose. The sub-fraction F2.4 reduced the cellular surface hydrophobicity. In this study was not possible verify the inhibition of extracellular enzymes activities. Combinations of sub-fraction F2.4 with amphotericin B, nystatin or fluconazole were not synergic. Through optic and scanning cletronic microscopy can be observed the inhibition in pseudohyphal formation and aggiutinant effect of sub-fraction F2.4. Irregularity on cell wall of yeasts treated was observed and transrnission eietronic microscopy showed evidence of the effect of "barbatimão" on yeast wall cdl. Additionally, the macrophage stimulation was verify when the yeasts were tu(ccI previously with 7.8 µg/mL of sub-fraction F2.4 by 2 h, observing increase of 28% iimpared with control group. Cytotoxicity effect ofextracts obtained from "barbatirnão" was hNeaved on Vero and rnacrophages celis with CC50 above 100 jig/mL. On the other hand, for hlood red ccli and Aflemia salina grub the CC50 and DL50 were >1,000 µg/mL, except for sub-fraction F2.4, which DL50 was 100 µg/mL. Probably the antifungal activity of sub-fraction 1 /4 is attributed the polyrners proanthocyanidins tri-hydroxylated in ring B and presence of acid Iinked in structure ofpolymer, with median molecular weight of 2,000 Da.